PERAN HUMAS DALAM MEMBANGUN CITRA POSITIF SMK BATIK 2 SURAKARTA - Leony Arum Dwi Putri; C. Dyah Sulistyaningrum I; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
The research aimed to find out: (1) How the role of public relations in building a positive image in SMK Batik 2 Surakarta. (2) Knowing the obstacles experienced by public relations in building a positive image at SMK Batik 2 Surakarta. (3) Knowing the public relations efforts to overcome obstacles in building a positive image at SMK Batik 2 Surakarta.This research is a qualitative research. The research data is collected from following sources: research participant, event, documents, and archives. The sampling technique used was purposive sampling. The techniques of data collection are interview, observation, and documentation. To check the validity of the data, the researcher uses source triangulation and method triangulation. Meanwhile the data is analysed based on the interactive analysis modelThe results of the study show: (1) that the implementation of the roles of public relations to build the school image of SMK Batik 2 Surakarta includes the roles of communicator, relationship maker, backup management, and corporate image maker. (2) The obstacles of public relations are public relations didn’t master the technique of conveying information or promotion. (3) The efforts to overcome obstacles is making an agenda for each public relations committee so that committee can carry out their duties properly as a public relations officer dan teacher.